Strategi FKUB Kota Bandung dalam Membangun Kerukunan Beragama demi Terciptanya Bandung Agamis: Suatu Studi Kasus - Abdullah Muslich Rizal Maulana; Fadhillah Rachmawati; Khalishah Imaniyyah; Khansa Fauziyyah; Malika Fildzah Nur Shabrina; Syakira Esa Rahimi Sari (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2023)
This article discussed the strategy of FKUB (Forum Kerukunan Umat Beragama) of Bandung City in building religious harmony for the community of Bandung City, aiming to realize ‘Bandung Agamis’ as a motto. This paper is qualitative field research with direct observation and interviewing methods to answer such research questions in examining problems. Based on this study, it is apparent that religious harmony must always be preserved in social life. Establishing this forum can minimize conflicts in Bandung so that harmony between religious people is formed. Moreover, this forum was formed by carrying out various strategies to preserve harmony in social life, such as organizing a dialogue between government figures and religious leaders and attending religious celebrations of people of other religions without participating in the rituals. This study concluded that harmony in Bandung could be realized with the coordination of FKUB, which has various strategies for achieving Bandung Agamis.